Analysis of nitrogenous organic compounds from mainstream cigarette smoke using low‐temperature solvent extraction followed by comprehensive two‐dimensional gas chromatography with high‐resolution time‐of‐flight mass spectrometry. Issue 15 (16th June 2015) - Xiang, Zhangmin; Cai, Kai; Zhou, Shuping; Geng, Zhaoliang; Pan, Wenjie
<x xml:space="preserve">Abstract</x> A method involving comprehensive two‐dimensional gas chromatography coupled to high‐resolution time‐of‐flight mass spectrometry was developed and applied to the analysis of nitrogenous organic compounds present in mainstream cigarette smoke trapped on self‐designed equipment. The samples were prepared using low‐temperature solvent extraction under liquid nitrogen and analyzed by comprehensive two‐dimensional gas chromatography with high‐resolution time‐of‐flight mass spectrometry. Important experimental parameters, such as the type and volume of the extraction solvent and flow rate of smoking, were optimized to improve the analysis parameter. The results indicated that 180 mL of diethyl ether in the low‐temperature solvent extraction apparatus system with a 4 mL/min smoke flow rate were the optimal conditions. Then, 85 nitrogenous organic compounds were identified and quantified using a mass spectral library search, accurate mass ion and N‐rules of a molecular formula for nitrogen compounds. Finally, a comparison of the low temperature solvent extraction method and Cambridge filter pad method indicated that more peaks, a higher peak volume and better repeatability were obtained using the low‐temperature solvent extraction method.